Revisiting the Future of International Marketing Strategy in the Digital Age - Agusta, Muhammad Adrian; Yusnidar, Yusnidar (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This paper explores the opportunities and challenges of the digital era in international marketing strategy. Focus on designing and implementing internet-based strategies, including internal company factors, external environment, market selection, mix marketing, and strategic control. Conceptual study This compiles and analyzes factors that influence marketing international use of digital technology. Digital technology influences decisions on foreign market selection, implementation, and control of marketing strategies. This allows the company to design effective marketing programs, support​ the implementation of digital devices, and improve performance internationally. This study gives a framework Work for marketing strategy internationally digital based and identifies opportunities for future research​ in the digital era.